Просопографія як метод дослідження козацько-старшинських родів. (Zaporizhzhia Historical Review, 2021)
The article demonstrates the possibilities of prosopographic method (method of researching colective biographies by considering every person that corresponds to the researcher’s field of scientific interest as an individual personality) in researching Cossack Starshyna.